Effects of different doses of sodium monensin on feeding behaviour, dry matter intake variation and selective consumption of feedlot Nellore cattle - Pereira, Murillo Ceola Stefano [UNESP]; Carrara, Tassia Veluma Barbosa [UNESP]; Silva, Juliana da [UNESP]; Silva, Diego Piovezan [UNESP]; Watanabe, Daniel Hideki Mariano [UNESP]; Tomaz, Lais Aquino [UNESP]; Arrigoni, Mario de Beni [UNESP]; Millen, Danilo Domingues [UNESP] (Csiro Publishing, 2015)
The experiment was designed to determine the effects of different doses of sodium monensin (MON) on feeding behaviour, dry matter intake (DMI) variation and selective consumption of feedlot Nellore cattle. The experiment was a randomised complete block design, replicated 12 times, in which 60 20-month-old yearling Nellore bulls (402.52 +/- 33.0 kg) were fed the following different doses of MON (expressed in mg per kg, on a DM basis) in individual pens for 84 days: 0, 9, 18, 27 and 36. The adaptation program consisted of ad libitum feeding of two adaptation diets over a period of 14 days with concentrate level increasing from 68% to 84% of diet DM. Orthogonal contrasts were used to assess linear, quadratic, cubic and quartic relationships between doses of MON and the dependent variable. As the dose of MON increased, the time spent ruminating (P < 0.01), feeding efficiency of DM (P < 0.05) and feeding efficiency of neutral detergent fibre (NDF; P < 0.05) were affected linearly during the period of adaptation. For the finishing period, as the dose of MON increased, time spent eating and ruminating, and feeding efficiency of DM were affected quadratically (P < 0.05), in which animals fed 9 ppm of MON presented better feeding efficiency of DM. Thus, as animals fed 9 ppm of MON presented better feeding efficiency of DM and NDF during the adaptation and finishing periods, it should be the dose of choice for feedlot Nellore cattle.
Keywords: Acidosis; Efficiency; Fluctuation